Individual Differences and Tourist Wayfinding Behaviours - Xia, Jianhong (Cecilia); Packer, D.; Dong, Jonathan (Modelling and Simulation Society of Australia and New Zealand and International Assn for Mathematics and Computers in Simulation, 2009)
The aim of the paper is to ascertain if tourist wayfinding behaviours correlate with individual differences. Individual differences in this study refer to age, gender, type of travel group and familiarity with the environment. The specific tourist wayfinding behaviours of in this paper are utilising landmarks and wayfinding strategies.. The methods used to identify the individual differences are Pearson Chi-square test and Odds ratio. Pearson Chi-square test is used to identify the significant differences and Odds ratio measures strength of association. A case study was conducted at the Koala Conservation Centre at Phillip Island Nature Park, Victoria, Australia. Differences in wayfinding behaviours between gender, age group, type of travel group and level of familiarity with the environment are identified. Females tend to follow a crowd and are more likely to use wayfinding strategies such as Least Time, First Noticed, and Different from Previous Route Taken than males. Males are more likely than females to use Vegetation Types and Track Surfaces as their wayfinding landmarks, and they prefer Most Scenic wayfinding strategies.When age is considered, the middle aged tourist group tends to find its destination based on a Shortest Path strategy while younger tourists prefer First Notice wayfinding strategies. Furthermore, tourists who are familiar with the environment are more likely than others to navigate using Shortest Path and Few Turns wayfinding strategies. Understanding individual differences among tourist wayfinding behaviours can be beneficial in developing wayfinding systems/devices that can assist tourists as they move from attraction to attraction within a tourist site. In addition, this information will be useful in park or urban design. In the future, we compare individual differences in tourist wayfinding behaviours with tourists’ physical movements as tracked by GPS. The key question is how the individual differences of tourist wayfinding behaviours influence tourists’ physical movements.